1984
DOI: 10.1111/j.1445-5994.1984.tb03753.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions of Body Weight, Age, Cigarette Smoking and Hormone Usage With Blood Pressure and Plasma Lipids in an Australian Community

Abstract: The predicted variation of blood pressure and plasma lipid levels, based on association with body weight, age, cigarette smoking and oral contraceptive usage, was examined in 47 000 self-referred subjects who attended a community programme for coronary risk factor screening. In both sexes, blood pressure and plasma lipid (cholesterol and triglyceride) levels were positively correlated with age and body mass index (BMI, kg/m2). Plasma triglyceride concentrations were positively correlated with cigarette smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In most studies, however, the effects of such important confounding factors were not considered thoroughly. In our review of the literature we have found studies that were adjusted for age and obesity, [7][8][9]12,13,19,[23][24][25][26] alcohol consumption, 14,24,25 physical activities 8,9,26 blood chemistry. 14,24,25 Most studies were adjusted for age and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies, however, the effects of such important confounding factors were not considered thoroughly. In our review of the literature we have found studies that were adjusted for age and obesity, [7][8][9]12,13,19,[23][24][25][26] alcohol consumption, 14,24,25 physical activities 8,9,26 blood chemistry. 14,24,25 Most studies were adjusted for age and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Different groups have reported that no association existed between smoking habit and blood pressure, [5][6][7][8][9] that blood pressure of smokers was lower than that of non-smokers, [10][11][12][13][14][15][16] or that smoking raised blood pressure. [17][18] In addition, a dose-effect relationship between daily smoking amount and blood pressure was significant in some studies, [13][14][15] while others failed to confirm this finding.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, numerous reports have found that smoking reduces blood pressure (Higgins and Kjelsberg 1967;Seltzer 1974;Berglund and Wilhelmsen 1975;Goldbourt and Medalie 1977;Gofin et al 1982;Agner 1983;Savdie et al 1984;Green et al 1986;Rosengren and Wilhelmsen 1987;Green et al 1991;Imamura et al 1996;Okubo et al 2002;Nagahama et al 2004;Okubo et al 2004;Wang et al 2006). In contrast, several other reports have found that smoking raises blood pressure (Elliott and Simpson 1980;Dyer et al 1982;Bolinder and de Faire 1998), while still others failed to confirm any effect on blood pressure (Arkwright et al 1982;Criqui et al 1982;Lang et al 1983;Simons et al 1984). Few large epidemiological studies on the effects of smoking on blood pressure have considered the confounding effects of such factors as age, obesity, blood chemistry, lifestyle or working conditions.…”
mentioning
confidence: 93%
“…Thus, smoking is a major risk factor for atherosclerosis and coronary artery disease [11,12]. Various mechanisms leading to lipid alteration by smoking are: (a)nicotine results in increased secretion of hepatic free fatty acids and triglycerides along with VLDL-C in the blood stream by increasing the secretion of catecholamines and thus stimulating sympathetic adrenal system resulting in increased lipolysis [13]; (b)consumption of a diet lacking in fibre and cereal content but enriched with fat and cholesterol by smokers as compared to non-smokers [14]; (c) cigarette smoking is known to be associated with raised plasma Homocysteine level [15,16] which causes oxidative modification of LDL-Colesterol and decreases HDL-Cholesterol [17], several studies reported homocysteine inhibited Apo A-I protein expression and decreased HDL Cholesterol [18,19].…”
Section: Introductionmentioning
confidence: 99%